Preconditioning the EFIE on Screens - Urzua-Torres, C; Hiptmair, R (World Scientific, 2020)
We consider the electric field integral equation (EFIE) modeling the scattering of time-harmonic electromagnetic waves at a perfectly conducting screen. When discretizing the EFIE by means of low-order Galerkin boundary methods (BEM), one obtains linear systems that are ill-conditioned on fine meshes and for low wave numbers k. This makes iterative solvers perform poorly and entails the use of preconditioning.